Rapport building in student group work - ADEL, Annelie (Journal of pragmatics, 2011)
► Rapport building (communicative acts promoting social concord) is studied in group work. ► Corpus-based and discourse-analytical methods are combined. ► The primary material is student discussions from an online learning management system. ► Spoken face-to-face study group discussions are also considered. ► A taxonomy of rapport-building discourse functions is developed. How do students build rapport in online group work, especially if all they have to work with is asynchronous text? Taking this question as a point of departure, this paper presents research into the ‘interactional’ function in group work among university students, specifically investigating rapport-building language use, defined as communicative acts promoting social concord. Rapport building is examined in online student group work, using written material in the form of discussion board messages (from the Mid-Sweden Corpus of Computer-Assisted Language Learning). To help bring out what is characteristic of the online type of discourse, spoken face-to-face material also representing student–student interaction (from the Michigan Corpus of Academic Spoken English) is included. Frequency word lists based on the two sets of material were used in combination with concordancing in order to find which of the most frequent expressions functioned as rapport building, thus combining corpus-based and discourse-analytical methods. A taxonomy of rapport-building discourse functions was developed, containing four major categories: discourse-structuring, intratextual, face-saving and bonding units. Each of these covers specific discourse functions; in the case of bonding units, these are Agreeing; Aligning with in-group; Commiserating; Complimenting; Seeking agreement; Offering encouragement; Thanking; Responding to thanks; and Chatting.